The Role of Value Orientation in Satisfaction of Basic Psychological Needs and Academic Adaptation of Students - R.M. Shamionov (Moscow State University of Psychology and Education, 2024)
This study aims to clarify the role of value orientation in the satisfaction of basic needs and academic adaptation of students. It will allow us to set goals, which help to achieve psychological well-being. The study involved (N=390) students of pedagogical profiles of the university (35% men, 65% women), aged 17–22, average age 19,85, SD=3,17. The following methods were used in the study: A scale of satisfaction of basic needs (M.M. Johnston, S.J. Finney, 2010); a "Portrait value questionnaire" (S. Schwartz, 2012); a methodology for diagnosing academic adaptation (R.M. Shamionov, M.V. Grigorieva, E.S. Grinina, A.V. Sozonnik, 2022) and a questionnaire to establish socio-demographic characteristics. It is established that the preservation and openness values are positive predictors of satisfaction of basic psychological needs as an personal autonomy, competence and connection with others. The positive effect of preservation values and the negative effect of openness on variations in academic adaptation is mediated by satisfaction of basic needs for autonomy and competence, which respectively enhance or reduce these effects.